Enhancing Indonesia’s Law Enforcement: Integrating Financial Investigations to Combat Human Trafficking Networks - Herbin Marulak Siahaan; Nimerodi Gulo (KRTHA BHAYANGKARA, 2026)
This study examines Indonesia’s efforts to combat human trafficking by integrating financial investigations into the enforcement approach. Although Indonesia has established a legal framework aligned with international standards, enforcement remains weak due to institutional fragmentation, limited investigative capacity, and a prosecutorial focus confined primarily to low-level offenders. Unlike prior studies that examine Indonesia’s anti-trafficking law or its anti-money laundering regime separately, this study is among the first to empirically test their intersection through Indonesian judicial decisions, applying the Financial Approach Theory and the Conjunction of Criminal Opportunity Theory as an integrated analytical lens. This dual approach reveals not only that enforcement gaps exist but also precisely where in the prosecutorial chain the follow-the-money mandate breaks down. Using qualitative doctrinal and socio-legal analyses of statutes, case law, and institutional practice, the study finds that financial investigation and asset confiscation are routinely overlooked, allowing traffickers to retain profits and sustain their operations. It argues that closing this gap requires mandatory financial investigation, stronger inter-agency coordination, victim-sensitive approaches, and deeper international cooperation, each of which is essential for dismantling trafficking networks and meeting Indonesia’s international obligations.